Clostridium difficile bacteremia: Report of two cases in French hospitals and comprehensive review of the literature. (2017) - Doufair, Mouna; Eckert, Catherine; Drieux, Laurence; Amani-Moibeni, Come; Bodin, Liliane; Denis, Michel; Grange, Jean Didier; Arlet, Guillaume; Barbut, Frédéric
Abstract: We report two cases of bacteremia due to Clostridium difficile from two French hospitals. The first patient with previously diagnosed rectal carcinoma underwent courses of chemotherapy, and antimicrobial treatment, and survived the C. difficile bacteremia. The second patient with colon perforation and newly diagnosed lung cancer underwent antimicrobial treatment in an ICU but died shortly after the episode of C. difficile bacteremia. A review of the literature allowed the identification of 137 cases of bacteremia between July 1962 and November 2016. Advanced age, gastro-intestinal disruption, severe underlying diseases and antimicrobial exposure were the major risk factors for C. difficile bacteremia. Antimicrobial therapy was primarily based on metronidazole and/or vancomycin. The crude mortality rate was 35% (21/60).